Calibration Approach for Variance Estimation of Small Domain. (28th August 2022) - Ashutosh, Ashutosh; Shahzad, Usman; Ahmad, Ishfaq; Ahmad Raza, Muhammad; Benedict, Troon J.
Abstract : The population parameters are estimated using sample surveys. However, the current investigation's goal is to estimate subpopulations parameters such as total through a calibration approach. The proposed estimator's properties have been given under simple random sampling. In addition, the class of estimators for subpopulation total has been discussed. The proposed estimator has been evaluated theoretically and empirically in a comparative study. The results demonstrated that a high-level estimate outperforms a low-level estimate for subpopulation total using a calibration approach.